Limited Access to Emotion Regulation Strategies Mediates the Association Between Positive Urgency and Sustained Binge Drinking in Patients with Alcohol Use Disorder. - Pepe, Maria; Di Nicola, Marco; Moccia, Lorenzo; Franza, Raffaella; Chieffo, Daniela; Addolorato, Giovanni; Janiri, Luigi; Sani, Gabriele (International Journal of Mental Health & Addiction, 2023)
Binge drinking (BD) represents a public health concern because of increasing prevalence, clinical implications, and social consequences. Determinants of BD have been mainly studied in non-clinical samples, but few data in patients with alcohol use disorder (AUD) are available. Our study aimed at identifying risk factors for BD in AUD patients. We evaluated 373 severe AUD outpatients, subdivided according to the presence of a sustained BD pattern in: non-binge drinkers (n = 256, M = 63.3%, 48.8 ± 10.7 years) and sustained binge drinkers (n = 117, M = 65%, 39.7 ± 9.6 years). We collected sociodemographic and clinical information and assessed impulsivity and emotion dysregulation using the short version of the UPPS-P Impulsive Behavior Scale (S-UPPS-P) and the Difficulties in Emotion Regulation Scale (DERS). We conducted a binomial logistic regression to investigate predictors for BD and a mediation analysis to test the effect of impulsivity and emotion dysregulation on BD. One hundred seventeen patients (31.4%) presented a sustained BD pattern. Positive urgency (OR: 2.235; p = 0.018) and limited access to emotion regulation strategies [DERS strategies (OR: 1.553; p = 0.004)] were risk factors for BD. The relationship between positive urgency and BD was significantly mediated by DERS strategies (p = 0.015; bootstrapped LLCI = 0.008, ULCI = 0.044). In our sample, positive urgency and limited access to emotion regulation strategies were risk factors for sustained BD in AUD patients. The effects of impulsivity on BD were mediated by difficulties in emotion regulation. BD patterns have been associated with poor response to treatment and worse outcome in AUD patients; however, the full impact of this problematic drinking pattern is still underinvestigated. Clarifying the underlying psychopathological dimensions is crucial to deliver targeted interventions.